Effect of phytase on availability of phosphorus to growing pigs - Khan, Naheeda (1995)
Problems caused by excessive phosphate output from the animal production sector were addressed by examining means of lowering phosphate excretion of growing pigs. A review of literature looked at the requirement, dietary allowance, and availability of phosphorus to growing pigs. Variation in estimated phosphorus requirements needed to be resolved before dietary allowances could be matched to requirements. It was recognised that phytate-phosphorus present naturally in cereals would be sufficient to meet the pig’s requirement for phosphorus if it could be hydrolysed prior to or during digestion. The use of Aspergillus niger phytase to improve phytate - phosphorus availability, and thereby lower faecal phosphate output, was explored. A series of trials assessed the efficacy of phytase from Aspergillus niger (var ficuum) and looked at the phosphorus requirement of growing pigs. The first studied the effects of phytase on apparent ileal and total tract digestibility, and examined whether an alteration in fermentation induced by dietary inclusion of yeast (Saccharomyces cerevisiae) could influence phosphorus availability. Six gilts, cannulated at the terminal ileum, were used in a 3 x 3 latin square balance trial. A high-phytate barley based diet containing 4.7g phosphorus (2.3g present as phytate-phosphorus) was fed (1) as a control, (2) with 2.5g (1000 units) Aspergillus niger phytase/ kg or (3) with 5g Saccharomyces Cerevisiae yeast/ kg. For each period, a 10-day acclimatization to the diet was followed by a 5-day total faeces and urine collection period, and thereafter by a 5-day ileal sampling period. Phytase addition resulted in an increased apparent ileal digestibility of phosphorus from 0.259 to 0.387 (p = 0.094, s.e.d. = 0.054), an increased total tract digestibility from 0.0483 to 0.632( p = 0.074, s.e.d. = 0.070), and a 37% reduction in faecal phosphate output (p = 0.018). Any alteration in fermentation as a result of yeast addition did not influence phosphorus digestibility. It was concluded that the addition of 1000 phytase units/kg feed caused hydrolysis of phytate and therefore an improved availability of phytate phosphorus.